2010
DOI: 10.1111/j.1558-5646.2009.00944.x
|View full text |Cite
|
Sign up to set email alerts
|

The Coevolution of Human Hands and Feet

Abstract: Human hands and feet have longer, more robust first digits, and shorter lateral digits compared to African apes. These similarities are often assumed to be independently evolved adaptations for manipulative activities and bipedalism, respectively. However, hands and feet are serially homologous structures that share virtually identical developmental blueprints, raising the possibility that digital proportions coevolved in human hands and feet because of underlying developmental linkages that increase phenotypi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
79
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(86 citation statements)
references
References 68 publications
(113 reference statements)
6
79
1
Order By: Relevance
“…The protective buttressing hypothesis is entirely compatible with the hypotheses that the derived proportions of human hands evolved: (1) in response to selection for increased precision and strength of grasping associated with manual manipulation (Napier, 1965;Marzke, 1983;Marzke, 1997;Susman, 1979;Susman, 1998) and (2) in response to selection on the foot for terrestrial locomotion, which resulted in coevolution of the hand (Alba et al, 2003;Rolian et al, 2010). It seems reasonable that selection for improved terrestrial locomotion, manual dexterity and fighting performance may all have played a role in the evolution of the proportions of the hands of hominins.…”
Section: Introductionsupporting
confidence: 64%
See 2 more Smart Citations
“…The protective buttressing hypothesis is entirely compatible with the hypotheses that the derived proportions of human hands evolved: (1) in response to selection for increased precision and strength of grasping associated with manual manipulation (Napier, 1965;Marzke, 1983;Marzke, 1997;Susman, 1979;Susman, 1998) and (2) in response to selection on the foot for terrestrial locomotion, which resulted in coevolution of the hand (Alba et al, 2003;Rolian et al, 2010). It seems reasonable that selection for improved terrestrial locomotion, manual dexterity and fighting performance may all have played a role in the evolution of the proportions of the hands of hominins.…”
Section: Introductionsupporting
confidence: 64%
“…This is likely the result of selection for increased manual dexterity being released from the constraining influence of selection for performance in an arboreal environment (Alba et al, 2003). Alternatively, it has been suggested that the hand proportions of hominins may partially, or largely, be a pleiotrophic result of selection on the foot for terrestrial locomotion (Alba et al, 2003;Rolian et al, 2010). A third reason that human-like manual proportions appear in the fossil record coincident with evidence of habitual bipedalism is that sexual selection for improved fighting performance may have contributed to the evolution of both (Carrier, 2011;present study).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are compelling reasons to suspect that the proportions of the hominin hand were influenced by selection on the foot for terrestrial locomotion (Alba et al, 2003;Rolian et al, 2010). Hand proportions may also have been influenced by other unidentified developmental constraints, as well as other aspects of selection and/ or by genetic drift.…”
Section: Discussionmentioning
confidence: 99%
“…These hand proportions are generally thought to be crucial to the great manipulative skills of humans and are usually associated with tool manufacture and use (Napier, 1962;Marzke, 1997;Susman, 1998;Young, 2003;Almécija et al, 2010Almécija et al, , 2015. Recently, many of the derived proportions of the hominin hand have also been suggested to be a pleiotropic result of selection on the foot for terrestrial locomotion (Alba et al, 2003;Rolian et al, 2010). There are clear arguments suggesting that both of these factors played a role in the evolution of hominin hand proportions.…”
Section: Introductionmentioning
confidence: 99%